Floral resources foraged by Geotrigona Argentina (Apidae, Meliponini) in the Argentine Dry Chaco forest - Vossler, Favio Gerardo (2010)
This study is the first contribution to knowledge of the relationships between Geotrigona argentina and the plants of the Argentine Dry Chaco forest. A total of 1260 g of honey (corresponding to 146 pots) and 763 g of pollen (63 pots) stored in four underground nests was studied. The honey pots from each nest were homogenised and the four honey samples were analysed by melissopalynological methods, whereas the pollen pots were studied individually. Both classical counts and counts affected by the volume of the pollen types were carried out. Pollen data were statistically analysed. Additional data on both protein and lipid content is also provided. A total of 39 pollen taxa were identified. Pollen collection was focused on a few pollen taxa: Prosopis, Castela coccinea, Maytenus and Capparis; these taxa, together with Ziziphus mistol and Pisonia zapallo, were also important nectar sources. The preliminary results show that pollen collection varied seasonally, being most diverse in the summer when G. argentina incorporates herbaceous plants into its diet. The pollen collection spectrum of G. argentina is similar to that of other Trigonina bees in that the main plant species collected are a few large shrubs or trees, whose flowering consists of small and clustered flowers. Pots with large amounts of monofloral loads with pollen from only a few species suggests an organised foraging behaviour that includes the recruitment of foragers, such as that observed in other eusocial bees.